2020
DOI: 10.1093/jisesa/ieaa059
|View full text |Cite
|
Sign up to set email alerts
|

Collection and Rearing of Container Mosquitoes and a 24-h Addition to the CDC Bottle Bioassay

Abstract: Container mosquitoes (Diptera: Culicidae) oviposit their eggs in both natural and artificial containers. Many container mosquito species also serve as important vectors of disease-causing pathogens including Aedes aegypti, Ae. albopictus, and Ae. triseriatus. Control of these species can be done through the use of adulticide sprays. The efficacy of these treatments is highly dependent on the insecticide susceptibility status of the local mosquito populations. This paper provides protocols on collecting and rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Diet or food source affects development across a wide range of Diptera, including important vectors, such as Aedes albopictus (Diptera: Culicidae) (Parker, 2020), animal pests, such as horn flies ( Haematobia irritans , Diptera: Musidae) (Holderman et al, 2020), fruit flies such as Drosophila melanogaster (Diptera: Drosophilidae) (Yang, 2018), and beneficial insects, such as the secondary screwworm ( Cochliomyia macellaria F., Diptera: Calliphoridae) (Ahmad et al, 2006). In the present study, the positive correlation observed between yeast supplemented growth media and adult emergence of E. tenax suggest that an adequate growth medium is necessary for producing larger colonies, even if factors other than the growth medium might be important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diet or food source affects development across a wide range of Diptera, including important vectors, such as Aedes albopictus (Diptera: Culicidae) (Parker, 2020), animal pests, such as horn flies ( Haematobia irritans , Diptera: Musidae) (Holderman et al, 2020), fruit flies such as Drosophila melanogaster (Diptera: Drosophilidae) (Yang, 2018), and beneficial insects, such as the secondary screwworm ( Cochliomyia macellaria F., Diptera: Calliphoridae) (Ahmad et al, 2006). In the present study, the positive correlation observed between yeast supplemented growth media and adult emergence of E. tenax suggest that an adequate growth medium is necessary for producing larger colonies, even if factors other than the growth medium might be important.…”
Section: Discussionmentioning
confidence: 99%
“…Diptera: Culicidae)(Parker, 2020), animal pests, such as horn flies (Haematobia irritans, Diptera: Musidae)(Holderman et al, 2020), fruit flies such as Drosophila melanogaster (Diptera: Drosophilidae)(Yang, 2018), and beneficial insects, such as the secondary screwworm (Cochliomyia macellaria F., Diptera: Calliphoridae) (Ahmad…”
mentioning
confidence: 99%
“…Egg collections were made using several ovicups throughout each of the treatment areas. Ovicups were constructed using a 16 oz plastic cup and attaching seed germination paper to the inside of the cup using binder clips [40]. During the mosquito season, ovicups were deployed throughout the treatment areas and filled with water to encourage oviposition by container mosquitoes.…”
Section: Field Sites and Samplingmentioning
confidence: 99%
“…Rearing protocols described in [40] were followed when handling field collected samples. Briefly, the number of eggs on the field collected papers were assessed for viability and quantified to determine the number of viable eggs on each paper.…”
Section: Laboratory Handling and Rearingmentioning
confidence: 99%
See 1 more Smart Citation